Human Resource Management (HRM) Strategy in Improving Organisational Innovation - Susantinah, Nugrahini; Krishernawan, Indra; Murthada (PT. LITERASI SAINS NUSANTARA, 2023)
In the era of globalization and intensifying business competition, innovation has become the key to the sustainability and success of an organization. One critical factor that can influence an organization's ability to innovate is Human Resource Management (HRM). This research aims to examine HRM strategies in enhancing organizational innovation. The method involves a comprehensive review of literature using qualitative analysis, with the goal of achieving a thorough understanding of the subject from 2014 to 2023. The study's results indicate that, in enhancing organizational innovation through HRM strategies, effective HRM integration is necessary to empower employees and cultivate an organizational culture that supports creativity. Key steps such as skill development, competency enhancement, the implementation of incentive policies, and good performance management are essential elements in achieving this objective. The culture of innovation is not the result of a single policy but rather a collection of integrated HRM practices. This foundation consists of visionary leadership and open communication, which play a crucial role in motivating employees to actively participate in the innovation process. Therefore, the leader's role is highly crucial in directing the organizational vision towards innovation and designing appropriate HRM policies.